Anisotropic thermal expansion of Ni, Pd and Pt germanides and silicides. (15th June 2016) - Geenen, F A; Knaepen, W; Moens, F; Brondeel, L; Leenaers, A; Van den Berghe, S; Detavernier, C
Abstract: Silicon or germanium-based transistors are nowadays used in direct contact with silicide or germanide crystalline alloys for semiconductor device applications. Since these compounds are formed at elevated temperatures, accurate knowledge of the thermal expansion of both substrate and the contact is important to address temperature depending effects such as thermal stress. Here we report the linear coefficients of thermal expansion of Ni-, Pd- and Pt-based mono-germanides, mono-silicides and di-metal-silicides as determined by powder-based x-ray diffraction between 300 and 1225 K. The investigated mono-metallic compounds, all sharing the MnP crystal structure, as well as Pd2 Si and Pt2 Si exhibit anisotropic expansion. By consequence, this anisotropic behaviour should be taken into account for evaluating the crystal unit's cell at elevated temperatures.